2015
DOI: 10.1007/s11049-015-9318-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting distributional restrictions on prenasalized stops

Abstract: Previous studies on prenasalized stops (NCs) focus mainly on issues of derivation and classification, but little is known about their distributional properties. The current study fills this gap. I present results of a survey documenting positional restrictions on NCs, and show that there are predictable and systematic constraints on their distribution. The major finding is that NCs are optimally licensed in contexts where they are perceptually distinct from plain oral and nasal stops. I provide an analysis ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 42 publications
(41 reference statements)
1
15
1
Order By: Relevance
“…These findings for Tumbuka differ fromStanton's (2016) findings in her survey of phonetic studies, where the stop portion of ND was usually very short compared to the stop portion of NT (recallFigure 3). One would expect Tumbuka NTh to behave similar to what Stanton reports for NT sequences.…”
contrasting
confidence: 95%
“…These findings for Tumbuka differ fromStanton's (2016) findings in her survey of phonetic studies, where the stop portion of ND was usually very short compared to the stop portion of NT (recallFigure 3). One would expect Tumbuka NTh to behave similar to what Stanton reports for NT sequences.…”
contrasting
confidence: 95%
“…Herbert (1976) suggested that prenasalized segments should have the phonetic duration of a single segment, else they should be considered clusters of two segments. Studies of several languages have presented this kind of argument; see Stanton (2015) for a summary of this literature, and also Avram (2010), Rivera-Castillo (2013). For example, Maddieson (1989) shows that Fijian prenasalized consonant durations match those of voiceless stops and /l/, and durations of vowels before the various consonants are likewise similar.…”
Section: Phoneticsmentioning
confidence: 90%
“…It is uncontroversial that in prenasalized sounds, a nasal interval comes before an oral interval: the velum is first lowered, then raised (e.g. Burton, Blumstein & Stevens (1992), Beddor & Onsuwan (2003), Riehl (2008); see Stanton (2015) for additional references). Cohn & Riehl (2012) noted that in many Austronesian languages, vowels after prenasalized consonants are oral, while after nasals, vowels are nasalized; that is, the right edge of a prenasalized consonant is fully oral.…”
Section: Phoneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies have been used to motivate unnatural sound changes. The case of post-nasal devoicing (PND), for instance, has been analyzed variously as a phonetically motivated process (Solé 2012), a result of Ohala’s (1981) hypercorrection, and a case of perceptual enhancement (Stanton 2016b). Some proposals have also argued that PND is the result of a number of sound changes (Dickens 1984, Hyman 2001).…”
Section: Introductionmentioning
confidence: 99%